A second‐generation glucagon‐like peptide‐1 receptor agonist mitigates vomiting and anorexia while retaining glucoregulatory potency in lean diabetic and emetic mammalian models. Issue 10 (25th June 2020) - Borner, Tito; Shaulson, Evan D.; Tinsley, Ian C.; Stein, Lauren M.; Horn, Charles C.; Hayes, Matthew R.; Doyle, Robert P.; De Jonghe, Bart C.
Abstract: Aim: To develop a conjugate of vitamin B12 bound to the glucagon‐like peptide‐1 receptor (GLP‐1R) agonist exendin‐4 (Ex4) that shows reduced penetrance into the central nervous system while maintaining peripheral glucoregulatory function. Methods: We evaluated whether a vitamin B12 conjugate of Ex4 (B12‐Ex4) improves glucose tolerance without inducing anorexia in Goto‐Kakizaki (GK) rats, a lean type 2 diabetes model of an understudied but medically compromised population of patients requiring the glucoregulatory effects of GLP‐1R agonists without anorexia. We also utilized the musk shrew ( Suncus murinus ), a mammalian model capable of emesis, to test B12‐Ex4 on glycaemic profile, feeding and emesis. Results: In both models, native Ex4 and B12‐Ex4 equivalently blunted the rise in blood glucose levels during a glucose tolerance test. In both GK rats and shrews, acute Ex4 administration decreased food intake, leading to weight loss; by contrast, equimolar administration of B12‐Ex4 had no effect on feeding and body weight. There was a near absence of emesis in shrews given systemic B12‐Ex4, in contrast to reliable emesis produced by Ex4. When administered centrally, both B12‐Ex4 and Ex4 induced similar potency of emesis, suggesting that brain penetrance of B12‐Ex4 is required for induction of emesis. Conclusions: These findings highlight the potential therapeutic value of B12‐Ex4 as a novel treatment for type 2 diabetes devoid of weight loss and with reduced adverse effects and better tolerance, but similar glucoregulation to current GLP‐1R agonists.